LC-MS-MS development and validation for simultaneous quantitation of metformin, glimepiride and pioglitazone in human plasma and its application to a bioequivalence study - Sengupta, Pinaki; Bhaumik, Uttam; Ghosh, Animesh; Sarkar, Amlan Kanti; Chatterjee, Bappaditya; Bose, Anirbandeep; Pal, Tapan Kumar (Vieweg Verlag, 2009)
A simple, precise and reproducible liquid chromatography–tandem mass spectrometry method has been developed and validated according to the Food and Drug Administration guidelines for the simultaneous quantitation of antidiabetic drugs metformin, glimiperide and pioglitazone in human plasma using glipizide as an internal standard. Quantitation was performed on a triple quadrupole mass spectrometer employing electrospray ionization technique, operating in multiple reaction monitoring and positive ion mode. Inter-batch and intra-batch coefficient of variation across four validation runs for the quality control samples was less than 7%. The accuracy determined at quality control levels was within 92.81–105.13%. The method was applied to a bioequivalence study.